Demodex Folliculitis Presenting as Periocular Vesiculopustular Rash. (29th July 2013) - Yun, Samuel H.; Levin, Flora; Servat, Javier
Abstract: Purpose : To report an unusual case of Demodex folliculitis presenting as periocular vesiculopustular rash. Design : Case report. Results : A 68 year-old woman presented with a unilateral periocular rash that was initially treated by her primary ophthalmologist with topical steroids and antivirals. Slit-lamp examination revealed severe bilateral blepharitis, right greater than left, with waxy sleeves around the eyelashes. The diagnosis of Demodex infestation was considered. Treatment with daily lid scrub with polyhexamethylene biguanide (PHMB), 1, 2-hexanediol and 1, 2-octanediol (OCuSOFT PLUS) and erythromycin ointment twice a day resulted in complete resolution of the symptoms after 4 weeks. Conclusions : Ophthalmologists should be aware of Demodex and consider it in the differential diagnosis of periocular skin lesions.